2013
DOI: 10.3928/01477447-20130523-24
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Surgical Reduction and Fixation for Pipkin Type I Femoral Fractures

Abstract: The purpose of this study was to assess the effect of timing of large fragment fixation in patients with Pipkin type-I fractures. Patients with Pipkin type-I fractures from the authors' trauma center were prospectively observed between July 2007 and July 2010. Fragments that constituted more than one-fourth of the femoral head were included. Thirty-six patients were equally randomized to undergo emergent surgical reduction and fixation or secondary operative fixation after emergent closed reduction. No signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…Swiontkowski et al [11] compared an anterior to posterior approach for the treatment of Pipkin I and II fractures in a retrospective case matched study. To the authors’ knowledge, only two limited randomized studies on the topic exist [12, 13]. Apart from a single systematic review on the topic [1], the largest contemporary series of femoral head fractures in the literature evaluated 110 patients from multiple centers and surgeons, over a period of 36 years; only 30 patients in this group were treated with femoral head ORIF [14].…”
Section: Discussionmentioning
confidence: 99%
“…Swiontkowski et al [11] compared an anterior to posterior approach for the treatment of Pipkin I and II fractures in a retrospective case matched study. To the authors’ knowledge, only two limited randomized studies on the topic exist [12, 13]. Apart from a single systematic review on the topic [1], the largest contemporary series of femoral head fractures in the literature evaluated 110 patients from multiple centers and surgeons, over a period of 36 years; only 30 patients in this group were treated with femoral head ORIF [14].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal timing of surgery is still controversial. Some literature indicated worse outcomes for Pipkin fractures with delayed surgery compared with those who had immediate surgery[ 13 ]. However, other studies showed no statistically significant differences in outcome when comparing time of surgery with hip reduction, definitive operative intervention or the anatomic operative approach to injury[ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as for fracture larger than 1/3 of joint surface, it should be preserved and treated with internal fixation. Open reduction should be done as early as possible in Type-II since the fracture is always large in weight bearing area 14. The implants can be divided into metal screw and absorbable screw.…”
Section: Discussionmentioning
confidence: 99%
“…Open reduction should be done as early as possible in Type-II since the fracture is always large in weight bearing area. 14 The implants can be divided into metal screw and absorbable screw. The scholars who preferred absorbable screw believe that strength of absorbable screw is enough and the stress would be transferred to healing bone surface.…”
Section: Discussionmentioning
confidence: 99%